Social entrepreneurship and its significance for contemporary rural areas - Anna Waligóra (Economic and Environmental Studies (E&ES), 2019)
Social entrepreneurship is constituted of various market initiatives aimed at balancing the economic objective achieved with the so-called social goals. These initiatives are both top-down (e.g. non-for-profit companies established as a result of public-private partnerships), mixed (e.g. student co-operatives supported by enterprises) and bottom-up (e.g. social co-operatives of natural persons). The phenomenon of social entrepreneurship is located in the area of social economy considerations, although it seems to go beyond the framework set for this area of knowledge. This means that social enterprises do not submit to the commonly used economic accounts of the functioning of business entities. It also means that the measurement of the (social) value of their functioning is subject to constant discussion, both in the area of scientific knowledge and socio-economic practice. Social enterprises operating in rural areas constitute a special type of social economy entities. In addition to tasks related to economic activity and the function of stimulating social capital of Polish villages, they seem to fulfil important tasks in the area of strengthening the transformation of Polish villages to modernity, both on the level of management and social activity. The paper presents the issue of social enterprises as an actual and potential tool to support the development of Polish rural areas. This issue is considered in the context of the theory of social costs, assuming the interdependence of all activities carried out in the so-called common space, and the theory of social capital, according to which the 'thicker' the network of social relations is, including the economic ones, the more the quality of life increases. Reference is also made to the original model of the Matrix of Social Enterprises, on the foundation of which the Matrix of Social Enterprises in Rural Areas is described. As a result of the conducted research, selected manifestations of social entrepreneurship of Polish villages are identified and described based on the Matrix of Social Entrepreneurship, both in the context of their historically rooted traditions, economic and social conditions and culture-forming functions. The paper formulates conclusions regarding the growing importance of social entrepreneurship for Polish countryside, especially with regard to the ability to create labor demand, market cooperation and social capital thickening. There was also formulated a positive assessment of the impact of social entrepreneurship on the contemporary rural areas.
Keywords: D90; Z13; Z14; 330; social economy; entrepreneurship; social enterprises; social capital; cooperative activity